Evaluation of an outreach programme for patients with COVID-19 in an integrated healthcare delivery system: a retrospective cohort study - Vincent Liu; Laura C Myers; Yi-Fen Irene Chen; Gabriel J Escobar; Catherine Lee; Brian L Lawson; Kathleen A Daly; Richard Dlott (BMJ Open)
Objectives In the first year of the COVID-19 pandemic, health systems implemented programmes to manage outpatients with COVID-19. The goal was to expedite patients’ referral to acute care and prevent overcrowding of medical centres. We sought to evaluate the impact of such a programme, the COVID-19 Home Care Team (CHCT) programme.Design Retrospective cohort.Setting Kaiser Permanente Northern California.Participants Adult members before COVID-19 vaccine availability (1 February 2020–31 January 2021) with positive SARS-CoV-2 tests.Intervention Virtual programme to track and treat patients with ‘CHCT programme’.Outcomes The outcomes were (1) COVID-19-related emergency department visit, (2) COVID-19-related hospitalisation and (3) inpatient mortality or 30-day hospice referral.Measures We estimated the average effect comparing patients who were and were not treated by CHCT. We estimated propensity scores using an ensemble super learner (random forest, XGBoost, generalised additive model and multivariate adaptive regression splines) and augmented inverse probability weighting.Results There were 98 585 patients with COVID-19. The majority were followed by CHCT (n=80 067, 81.2%). Patients followed by CHCT were older (mean age 43.9 vs 41.6 years, p<0.001) and more comorbid with COmorbidity Point Score, V.2, score ≥65 (1.7% vs 1.1%, p<0.001). Unadjusted analyses showed more COVID-19-related emergency department visits (9.5% vs 8.5%, p<0.001) and hospitalisations (3.9% vs 3.2%, p<0.001) in patients followed by CHCT but lower inpatient death or 30-day hospice referral (0.3% vs 0.5%, p<0.001). After weighting, there were higher rates of COVID-19-related emergency department visits (estimated intervention effect −0.8%, 95% CI −1.4% to −0.3%) and hospitalisation (−0.5%, 95% CI −0.9% to −0.1%) but lower inpatient mortality or 30-day hospice referral (−0.5%, 95% CI −0.7% to −0.3%) in patients followed by CHCT.Conclusions Despite CHCT following older patients with higher comorbidity burden, there appeared to be a protective effect. Patients followed by CHCT were more likely to present to acute care and less likely to die inpatient.